2009
DOI: 10.1002/jez.582
|View full text |Cite
|
Sign up to set email alerts
|

Skin peptides of different life stages of Ewing's tree frog

Abstract: In frogs, an important mechanism of skin innate immunity against invading microbial pathogens is secretion of antimicrobial peptides from the specialized granular glands. Since these glands develop fully in skin dermis after completion of metamorphosis, they are small and immature in skin of larvae (tadpoles). Skin secretions vary among different life stages. Antimicrobial activity and peptide composition of natural mixture of skin peptides of three different life stages of New Zealand Ewing's Tree Frog (Litor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
(39 reference statements)
1
15
0
Order By: Relevance
“…For example, RLS, an infectious disease caused by septicemia, was the main cause of frog mortality [3840]. Pathogens that increase the risk of RLS included Pseudomonas aeruginosa and Staphylococcus epidermidis [39, 40, 58]. Although, the RLS-related pathogens in brown tree frogs are still uncharacterized.…”
Section: Discussionmentioning
confidence: 99%
“…For example, RLS, an infectious disease caused by septicemia, was the main cause of frog mortality [3840]. Pathogens that increase the risk of RLS included Pseudomonas aeruginosa and Staphylococcus epidermidis [39, 40, 58]. Although, the RLS-related pathogens in brown tree frogs are still uncharacterized.…”
Section: Discussionmentioning
confidence: 99%
“…It is has been suggested that every species harbors a unique, specific collection of antimicrobial peptides, tuned to defend the organism against microorganisms that it is likely to encounter. 13 As shown in Table 1, we do not seem to find any specific pattern, which assigns specific activities to certain habitats. In fact what seems to be the case is the opposite.…”
Section: Discussionmentioning
confidence: 59%
“…It is this line of though that directed our approach not towards individual substances but rather to a whole repertoire of substances that act in synergism, with the mixture having up to a 10-fold greater antibiotic activity than the peptides separately. 13,22 The methodology presented here allows for in vitro production, analysis and characterization of the 'natural mixture' of compounds secreted by different anuran species in order to cope with the highly hostile environment in which they live. In this respect it should be pointed out that some of the activities reported here, as shown in Figures 5 and 6, were very potent against various pathogenic bacteria without having any toxic effects on somatic cells even at 10-fold higher concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations